5-aminolevulinic acid induces regulation in growth, yield and physio-biochemical characteristics of wheat under water stress - Akram, Nudrat Aisha; Kausar, Shamim; Farid, Naila; Muhammad Ashraf,; Al-Qurainy, Fahad (Penerbit Universiti Kebangsaan Malaysia, 2018)
The production of wheat crop is below average in many regions of the world which is ascribed to adverse environmental conditions including drought stress. The present study was conducted to appraise the beneficial role of exogenouslyapplied 5-aminolevulinic acid (ALA) on growth, yield and some key physio-biochemical characteristics of two commercially important wheat cultivars (Shafaq-06 and Uqab-2000) under well watered [100% field capacity (FC)] and water-deficit (60 and 80% FC) conditions. Imposition of varying water regimes significantly decreased fresh and dry weights of shoots, photosynthetic pigments (a and b), non-photochemical quenching of chlorophyll fluorescence (NPQ), quenching coefficient for non-photochemical (N) of chlorophyll fluorescence (qN), K+ (potassium ion), Ca2+ (calcium ion) and P (phosphorus) accumulation in shoot and root and yield-related attributes. In contrast, water deficit regimes caused improvement in Fv/Fm (chlorophyll fluorescence measurement), coefficient of photochemical quenching (qP), proline, glycinebetaine (GB) and hydrogen peroxide (H2O2) contents. Foliar spray of ALA at the rate of 50, 100 and 150 mg/L along with control (no spray (NS) and/or water spray (WS)) significantly enhanced chlorophyll a and b pigments, qN, NPQ, qP, K+, Ca2+ and P accumulation in both roots and shoots, proline, GB, total phenolics and malondialdehyde (MDA) contents and yield. The wheat Shafaq-06 was better in shoot dry weight, qN, NPQ and Fv/Fm, shoot and root K+, root Ca2+, proline, GB accumulation and yield attributes, while Uqab-2000 was better in chlorophyll a contents, root P and MDA contents. Overall, better growth and yield of Shafaq-06 than Uqab-2000 under water deficit regimes was found to be associated with ALA improved leaf fluorescence (qN, NPQ and Fv/Fm), shoot and root K+, root Ca2+, proline and GB accumulation.